KEBIJAKAN DEREGULASI DALAM BIDANG PERBANKAN DI INDONESIA TAHUN 1983-1997 - Putra, Ramadan; Kurniawati, Kurniawati; Martha, Nur’aeni (Estoria: Journal of Social Science and Humanities, 2020)
This study discusses economic policies during the New Order era, especially theDeregulation Policy in the Banking Sector in Indonesia, which began in 1983 to1997. The method used in this research is the historical method and thepresentation of the research results is carried out in a descriptive-narrativeform. The results of this study explain that the Deregulation Policy in theBanking Sector which consists of five deregulation policy packages whichinclude the June 1, 1983 Package, the 28 October 1988 Package, the 29January 1990 Package, the 28 February 1991 Package and the 29 May 1993Package are quite successful in maintaining growth and development. theIndonesian economy after the fall in the price of petroleum to remain stable inaccordance with the development plan set by the New Order Government. Keywords: Deregulation, 1 June 1983 Policy, 28 October 1988 Policy, 29January 1990 Policy, 28 February 1991 Policy and 29 May 1993 Policy.